(untitled) (Training and Practice : Journal of Educational Sciences, 2017)
Beginning from the middle of the 1980ies a continuous improvement strategy has evolved in the Hungarian education, along which the changes focusing onto the democratic reorganisation of the education system could start. During this period in 1989 a research group was established in the Kindergartner Training Institute of Sopron, which has intended to realize the kindergarten adaptation of the reform pedagogy owing to the name of the French folk teacher, Célestin Freinet. As the result of the innovation thereof from September 1989 an alternative kindergarten program in the spirit of Freinet was realized at first in the country, with permission by the ministry. Owing to this initiative always more kindergartner at several points of the country has undertaken to adopt Freinet-pedagogy and to renew kindergarten education. In my study I would like to demonstrate the “experience worlds”, which were outlined from the statements of pedagogues. During my investigations I have explored the reasons and motivations hiding behind the demand and method of change and the adventures experienced during the adaptation of Freinet-pedagogy by using the method of qualitative content analysis.